OP0115 Efficacy of Belimumab in Systemic Lupus Erythematosus Patients with High Disease Activity in Key Organ Systems: Bliss Sub-Populations. (23rd January 2014) - Schmitt, C.; Roth, D.; Birch, H.; Kleoudis, C.; De Vries, J.
Abstract : Background: Decision-makers who treat SLE patients should understand the efficacy of new treatments in patients with the highest unmet need. Objectives: To assess the efficacy of belimumab in SLE patients with high disease activity, defined as evidence of renal, neurological, hematological or cardiovascular/respiratory involvement, anti-dsDNA+ and/or low complement at baseline. Methods: Data from 2 randomized, double-blind, multicenter studies (HGS1006-C1056: BLISS-52 and HGS1006-C1057: BLISS-76) were combined (GSK study BEL114246). The primary endpoint was the SLE Responder Index at Week 52. A logistic regression model was applied. Secondary endpoints included a ≥4 point reduction in SELENA-SLEDAI (SS) score at week 52, change in SF-36 physical component score (PCS) at week 24 and time to first flare after 24 weeks. Number of flares and the change from baseline at week 52 in mean Physician Global Assessment (PGA), EQ-5D, and FACIT-Fatigue scores were exploratory endpoints. Results: 1016 SLE patients (60%) met high disease activity criteria. Belimumab 1mg/kg and 10mg/kg plus standard care had significantly higher SRI response rates compared with placebo at Week 52 in this high disease activity group (Week 52: 45.9% and 49.6% belimumab 1 and 10mg/kg respectively vs. 33.6% placebo). Significantly more subjects had a ≥4 point reduction in SS from baseline compared with placebo (Week 52: 47.1% and 50.7% belimumab 1 and 10mg/kg respectively vs. 35.8% placebo). Improvements in SF-36 PCS for each belimumab dose were not statistically different from placebo (Week 24: 4.37 and 4.27 points belimumab 1mg/kg and 10mg/kg respectively vs. 3.67 placebo). Belimumab-treated subjects were 26%>34% less likely to have a disease flare after 24 weeks of treatment (modified SLE flare index) compared with placebo (HR 0.66, p-value <0.001 belimumab 1mg/kg and HR 0.74, p <0.01 10mg/kg respectively vs. placebo). Flares per subject year were also reduced (LS mean flares 4.81 placebo, 3.98 1mg/kg (p <0.001), 3.96 10mg/kg (p <0.001). Significant improvements in PGA score were observed from 8 weeks onwards with belimumab 10mg/kg vs. placebo (Week 52: 0.54 vs. 0.40 mean reduction respectively, p<0.0001). Significant improvements in FACIT- fatigue score were observed with 10mg/kg vs. placebo at weeks 8, 12, and 52 (Week 52: 4.72 point mean improvements 10mg/kg vs. 2.05 placebo, p<0.0007), but not at week 24. SF-36 PCS was significantly improved at week 52 (1mg/kg and 10mg/kg) vs. placebo as were the sub-domains of physical functioning, bodily pain, vitality and social functioning. Significant improvements from baseline in EQ-5D were observed at week 8, 24, and 52 with 10 mg/kg vs. placebo (Week 52: 0.10 vs. 0.05 mean score improvement respectively (UK value set), p=0.0011) but not at week 12. Conclusions: Patients with SLE and high disease activity in key organ systems reported substantial efficacy, decreased flare rate, and improvements in patient and physician reported measures of wellness with belimumab 10 mg/kg after 52 weeks of treatment. Acknowledgements: Human Genome Sciences, Rockville, Maryland, USA, was involved in study conception, design, implementation, and supervision; data analysis and interpretation; and statistical analyses. GSK was involved in data analysis and interpretation; statistical analyses; and abstract drafting and revision. Disclosure of Interest: C. Schmitt Shareholder of: GSK, Employee of: GSK, D. Roth Shareholder of: GSK, Employee of: GSK, H. Birch Shareholder of: GSK, Employee of: GSK, C. Kleoudis Shareholder of: GSK, Employee of: GSK, J. De Vries Shareholder of: GSK, Employee of: GSK